Pattern and Visual Outcome of Ocular Trauma Presenting to the Emergency Department of Swat Medical Complex Teaching Hospital - Jamal Hussain, Abshar Ahmad, Nawab Ali Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Ocular trauma is a major cause of visual impairment and preventable blindness worldwide, particularly in developing countries. Understanding the pattern and outcomes of eye injuries is essential for improving management and prevention strategies. Objective: To evaluate the pattern of ocular trauma and assess the visual outcomes among patients presenting to the emergency department. Methods: This was a hospital-based descriptive cross-sectional study conducted at Swat Medical Complex Teaching Hospital from January 2021 to January 2022 including 85 patients presenting with ocular trauma to the emergency department. Patients with any form of eye injury presenting to the emergency unit were enrolled Results: The mean age of patients was 27.6 ± 14.2 years, with males accounting for 71.8% of cases. Domestic accidents (28.2%) and occupational injuries (24.7%) were the most common causes of trauma. Closed globe injuries were more frequent (61.2%) than open globe injuries (38.8%). The mean time to presentation was 13.4 ± 7.6 hours. Severe visual impairment at presentation was observed in 47.1% of patients. Following management, visual improvement occurred in 45.9% of cases. Conclusion: Ocular trauma predominantly affects young males and is commonly associated with domestic and occupational injuries. Early diagnosis, prompt treatment, and preventive measures are crucial for improving visual outcomes and reducing the burden of ocular trauma. Keywords: Ocular trauma; Visual outcome; Eye injuries; Closed globe injury; Open globe injury; Emergency ophthalmology.